DOI: 10.31274/etd-180810-5563
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid and gibberellin control of plant height in maize (Zea mays. L)

Abstract: Brassinosteroids (BRs) and gibberellins (GAs) are two major plant hormones involved in many plant developmental processes. However, the knowledge of BR and GA control of agronomic traits in maize is limited compared to model species Arabidopsis and rice, especially BR. This PhD project focused on BR and GA control of plant height from genetics and plant biology perspectives, as these two plant hormones have shown great impact for shaping plant height, and a short/tall stature of maize height is beneficial for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
2
2
0
Order By: Relevance
“…The nine lines were BGEM-0005-N, BGEM-0085-N, BGEM-0107-N, BGEM-0129-N, BGEM-0132-N, BGEM-0215-N, BGEM-0227-N, BGEM-0232-N, and BGEM-0248-N. The misclassification within sub-populations is in accordance with the findings of Hu (2016) and is most likely due to the exotic germplasm contribution of the BGEM lines.…”
Section: Population Structuresupporting
confidence: 78%
“…The nine lines were BGEM-0005-N, BGEM-0085-N, BGEM-0107-N, BGEM-0129-N, BGEM-0132-N, BGEM-0215-N, BGEM-0227-N, BGEM-0232-N, and BGEM-0248-N. The misclassification within sub-populations is in accordance with the findings of Hu (2016) and is most likely due to the exotic germplasm contribution of the BGEM lines.…”
Section: Population Structuresupporting
confidence: 78%
“…Recent studies have shown that the GSK3 family or their corresponding BR hormones have been emerging as an important genetic engineering targets or plant growth regulators in numerous crops like rice (Oryza sativa) [17,32] and maize (Zea mays. L) [33]. In grapevine, GSK3 homolog VvSK1 is reported as a sugar-inducible protein kinase that regulates hexose transport and sugar accumulation in cultured grapevine cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…The nine lines were BGEM-0005-N, BGEM-0085-N, BGEM-0107-N, BGEM-0129-N, BGEM-0132-N, BGEM-0215-N, BGEM-0227-N, BGEM-0232-N, and BGEM-0248-N. The misclassification within sub-populations is in accordance with the findings ofHu (2016).…”
supporting
confidence: 86%